A sikondai gyógyfürdő az államosítás előtt és után: THE SIKONDA SPA BEFORE AND AFTER THE NATIONALIZATION - Nyári, Tamás (Közép-Európai Közlemények, 2022)
After the communist takeover, by the end of the 1940s, the previously privately owned spas had fallen into state hands. This was also the fate of the Harkány and Sikonda spas in Baranya County. In 1928, the Salgótarján Coal Mine Company searched for coal in the forest of the Parish of Székesegyház in Pécs, when it found the thermal water source at a depth of 318 meters. The forest councilor of Székesegyház, Andor Kolossváry, recognizing the potential of the spring, using the analysis of the chief chemist of the Danube Steamboat Shipping Company, opened a spa, in the first temporary pool of which 18,000 guests bathed in the first year. In the years that followed, its guests came in part from the ranks of the surrounding mining population, who largely treated their rheumatic ailments here. At the same time, the majority of the guests came from circles that were more able to afford higher prices. The years 1948-49 marked a turning point in the history of the spa, which gained the status of a healing spa from 1935. The nationalization of the spa and the transformation of the hotel into a night sanatorium can be done during this period. From 1963, a mining sanatorium, which was definitely engaged in healing, also operated here. Sikonda’s institution was 64 Nyári T.: A sikondai gyógyfürdő az államosítás előtt és után not unique in the country, but it became one of the most significant, in many cases exemplary, mining medical centers.